The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1046/j.1365-2044.1999.00665.x
|View full text |Cite
|
Sign up to set email alerts
|

Radicular acute pain after epidural anaesthesia with the technique of loss of resistance with normal saline solution

Abstract: SummaryFatal oesophageal perforation occurred as a complication of elective general anaesthesia for cataract extraction in a 77-year-old female patient. Tracheal intubation had been achieved, albeit with difficulty, in the course of a clinical trial of the intubating laryngeal mask.Keywords Equipment; intubating laryngeal mask. Complications. ...................................................................................... Correspondence to: Dr M. A. Branthwaite Accepted: 30 May 1998 The laryngeal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Moreover, at least some of these complications have been reported after LOR to saline. 16 We did find a small but statistically significant increase in the number of attempts required to locate the epidural space with LOR to air compared with saline. There are several possible explanations.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, at least some of these complications have been reported after LOR to saline. 16 We did find a small but statistically significant increase in the number of attempts required to locate the epidural space with LOR to air compared with saline. There are several possible explanations.…”
Section: Discussionmentioning
confidence: 59%
“…Epidural air can spread along the nerves of the paravertebral space, and, depending on its location, neurologic complications such as multiradicular syndrome, lumbar root compression, and even paraplegia can occur [7,8]. Kennedy et al [8] reported a case of back pain and paraplegia due to an erroneous injection of massive air in the epidural space during continuous lumbar epidural infusion of opioids and local anesthetics to treat cancer pain.…”
Section: Discussionmentioning
confidence: 99%
“…The most common etiology in these symptomatic cases was diagnostic or anesthetic intervention to the spine (n ¼ 8). 18,[30][31][32][33][34][35][36] Neurologic symptoms in four patients were associated with pneumothorax or pneumomediastinum caused by thorax trauma and lobectomy for small-cell carcinoma of the lung. 20,[37][38][39] Two patients' neurologic symptoms were associated with pneumocephalus caused by head trauma and a suboccipital craniotomy for foramen magnum meningioma, respectively.…”
Section: Symptomatologymentioning
confidence: 99%
“…Recent studies have shown that PR itself can cause neurologic symptoms ranging from radicular pain to cauda equina syndrome. [30][31][32][33][34][35] A literature search disclosed 19 cases in which the patient exhibited one or more symptoms. Of these 19 patients, 10 presented with weakness, 7 with sensory loss, and 7 with radicular pain (►Table 1).…”
Section: Symptomatologymentioning
confidence: 99%